Pengembangan Majalah Anak Materi Ekosistem Dalam Meningkatkan Literasi Sains Siswa Kelas V Sekolah Dasar - Agung Wahid Surya Dadari; Surayanah Surayanah (Cetta: Jurnal Ilmu Pendidikan, 2026)
The low level of science literacy among students in Indonesia in 2022, with a score of 383, as well as the results of observations and interviews with teachers at SDN 4 Karangtengah and SDN 2 Kepanjenlor, show that student science literacy is a serious challenge. This condition is reinforced by school policies that do not allow the use of gadgets as digital learning resources, thus requiring non-digital media. The study aimed to develop a children's magazine on ecosystems by integrating valid, practical, and effective PISA science literacy indicators to improve students' science literacy. The research was conducted using an R&D model with the ADDIE development model. The research subjects were one validator for each expert, two fifth-grade teachers, and 36 fifth-grade students from two schools. Data were obtained from the assessment of subject matter experts, media, and instruments, the completion of practicality questionnaires by teachers and students, and the administration of pre-tests and post-tests. The results showed that the children's magazine on ecosystem material had high validity, with an average validation score of 100% for the material, 92.3% for the media, and 92.5% for the test instruments. The achievement of the maximum score by subject matter experts identified that the material met the validation instrument criteria with a rating scale of 1-4. It should be noted that this score was obtained after making improvements based on the suggestions and input from subject matter expert validators. The level of practicality received a score of 94.3% on the student questionnaire and 95.8% on the teacher questionnaire, which means that the children's magazine is very practical. Its effectiveness is evident from the N-Gain score of 0.80 or 80%, indicating a high and effective category. In addition, the children's magazine has a significant effect on improving science literacy, as evidenced by the Wilcoxon test results with a score of 0.000. Thus, it can be concluded that the children's magazine on the ecosystem is able to improve the science literacy of fifth-grade students.